Perencanaan Strategi Sistem Informasi: Studi Kasus Perusahaan Asuransi Jiwa - Idris Gautama; Meirianty Prawira; Vianty Prawira (Bina Nusantara University, 2001)
Article explain the common needs of information system in certain life insurance companies, then derive to propose the Strategic Planning on the Information System. At the beginning, this paper gives overview on what and how information and its planning in general, then explain the process how to build a strategic planning of information system and last propose the strategic planning itself.